ANALISIS STRATEGI MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA PEGAWAI DI KANTOR BADAN PENANGGULANGAN BENCANA DAERAH KOTA GUNUNGSITOLI - Erwinman Telaumbanua; Palindungan Lahagu; Odaligoziduhu Halawa; Meiman Hidayat Waruwu (Jurnal Publikasi Manajemen Informatika, 2026)
This study aims to analyze Human Resource Management (HRM) strategies in improving employee performance at the Regional Disaster Management Agency (BPBD) of Gunungsitoli City. The focus of the study includes the HRM strategies implemented, the challenges encountered in their implementation, and the optimization efforts undertaken to enhance employee performance. This research employed a qualitative approach with a descriptive research design. The informants consisted of the Head of BPBD, the Head of the General Affairs and Personnel Subdivision, and several division heads directly involved in human resource management. Data were collected through interviews, observations, and documentation. Data analysis was conducted using the Miles, Huberman, and Saldaña model, which includes data reduction, data display, and conclusion drawing. The findings indicate that HRM strategies at BPBD Gunungsitoli City are implemented through organizational structure strengthening, employee competency development through training and disaster simulation programs, competency-based job assignments, performance evaluation using work performance indicators, and the utilization of technology in personnel administration. However, the implementation of these strategies still faces several challenges, including budget limitations, the lack of continuous training programs, inadequate reward systems, promotion practices that are not fully competency-based, the absence of an integrated personnel information system, and a work culture that has not fully embraced professionalism and collaboration. Optimization efforts required include the development of a competency development roadmap, enhancement of the quality and frequency of training programs, strengthening performance-based reward and promotion systems, digitalization of HR management processes, and fostering a professional and performance-oriented work culture. This study concludes that the HRM strategies implemented by BPBD Gunungsitoli City have contributed to improving employee performance. However, further improvements are needed through competency enhancement, the implementation of a merit-based system, and the utilization of information technology to support organizational effectiveness in carrying out disaster management responsibilities.